2017
DOI: 10.1002/rcm.7961
|View full text |Cite
|
Sign up to set email alerts
|

Does low‐energy collision‐induced dissociation of lithiated and sodiated carbohydrates always occur at anomeric carbon of the reducing end?

Abstract: Our data shows that dehydration reactions and cross ring dissociation do not always occur at the anomeric carbon atom of the reducing monomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
(70 reference statements)
1
22
0
Order By: Relevance
“…However, in the process of LODES, the first step is to generate the fragment by dehydration or cross‐ring dissociation at the reducing end, such that B (or C) ions can be differentiated from Z (or Y) ions in subsequent dissociation. Our previous study showed that dehydration and cross‐ring dissociation from the nonreducing end of oligosaccharide lithium adducts were not negligible, compared with sodium adducts; therefore, labeling of the O1 atom of the sugar at the reducing end by 18 O is necessary for some oligosaccharides if lithium adducts are used.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the process of LODES, the first step is to generate the fragment by dehydration or cross‐ring dissociation at the reducing end, such that B (or C) ions can be differentiated from Z (or Y) ions in subsequent dissociation. Our previous study showed that dehydration and cross‐ring dissociation from the nonreducing end of oligosaccharide lithium adducts were not negligible, compared with sodium adducts; therefore, labeling of the O1 atom of the sugar at the reducing end by 18 O is necessary for some oligosaccharides if lithium adducts are used.…”
Section: Resultsmentioning
confidence: 99%
“…In positive ionization mode, adduct ions formed with cations may have different origins and may result from: the protonation of a basic site of an entity already existing as a salt; the charge solvation of a metal cation by the lone‐pair(s) of heteroatom(s) of either (A) a molecule or (B) a salt. Representative examples of such adduct ions possibly formed with glucose and sodium cations are depicted in Figure as well as the corresponding proposed annotation.…”
Section: Illustrative Examples and Discussionmentioning
confidence: 99%
“…In positive mode, adduct ions such as [M + Na] + in their charge‐solvated form usually dissociate with regeneration of the alkali cation . In contrast, the ionized salts are much more stable species and can only dissociate under higher desolvation conditions.…”
Section: Illustrative Examples and Discussionmentioning
confidence: 99%
“…The new method involves the sequential low-energy resonance excitation CID experiments of sodiated oligosaccharides in a typical ion trap mass spectrometer. However, the sequence of the tandem CID experiment is specially designed according to the dissociation mechanism we found recently 38 , 39 , and the measured CID spectra are compared with our specially prepared database. In the following sections, we first describe the dissociation mechanism, followed by a description of the database and the scheme of the procedure to determine the structures of oligosaccharides.…”
Section: The Approach Of De Novo Structural Determinationmentioning
confidence: 99%
“…Recent high-level quantum chemistry calculations 12 , 38 , 39 have indicated that glycosidic bond cleavage, cross-ring dissociation and dehydration reactions on the reducing sugar are dissociation channels with low barrier heights for sodiated carbohydrates. By contrast, cross-ring dissociation and dehydration reactions on the nonreducing sugar are dissociation channels with high barrier heights.…”
Section: The Approach Of De Novo Structural Determinationmentioning
confidence: 99%